Early Discharge Does Not Increase Readmission Rates After Minimally Invasive Anatomic Lung Resection. Issue 3 (May 2019) - Chevrollier, Guillaume S.; Nemecz, Amanda K.; Devin, Courtney; Go, Kendrick V.; Yi, Misung; Keith, Scott W.; Cowan, Scott W.; Evans, Nathaniel R.
Abstract : Objective: Enhanced recovery pathways reduce length of stay and costs following lung resection. However, many fear that early discharge may lead to increased hospital readmissions. In this study, we aimed to determine whether early discharge was associated with increased readmission following anatomic lung resection. Methods: Using the lung resection database approved by our institutional review board, we identified all patients undergoing minimally invasive lobectomy and segmentectomy between January 2010 and March 2017 at our institution, where an enhanced recovery pathway is well established. Thirty-day readmissions were compared between patients with short- and average length of stay, defined as 1 to 2 days and 3 to 5 days, respectively. Multivariable logistic regression analysis of patients matched by propensity scores was performed to determine odds of 30-day readmission for each group. Significance was set at P < 0.05. Results: A total of 296 patients met inclusion criteria. Unadjusted analysis revealed a 3-fold increased rate of readmission in the group with average length of stay (9%, n = 12) versus the group with short length of stay (3%, n = 5; P < 0.01). At baseline, patients with average length of stay had increased rates of preoperative chemotherapy (13%, n = 18 vs. 4%, n = 6; P < 0.01) and radiation (12%, n = 16 vs. 3%, n = 5). Patients with average length of stay also had higher rates of lobectomy (95%, n = 127 vs. 86%, n = 140; P = 0.02) and postoperative complications (31%, n = 41 vs. 4%, n = 7; P < 0.01). On multivariable analysis, patients with average length of stay had a 2.3-fold greater odds of readmission, which was not statistically significant (OR = 2.33; 95% CI, 0.60 to 9.02; P = 0.22). Conclusions: Early discharge following minimally invasive anatomic lung resection does not increase the risk of hospital readmission in patients treated within an enhanced recovery pathway.